CORRELATION OF PARENT RELATIONSHIP AND RELIGIOUS GUIDANCE IN SCHOOL WITH LEADERSHIP STUDENTS IN MADRASAH TSANAWIYAH NEGERI (MTsN) DEPOK - Haris Fadillah; Muhyani .; Kholil Nawawi (UNIVERSITAS PAKUAN, 2019)
Parenting is an illustration of the attitudes and behavior of parents and children in interacting, communicating during holding parenting activities. In the activity of providing this care, parents will give attention, regulations, discipline, gifts and punishments, as well as responses to the wishes of their children. Parents' attitudes, behaviors, and habits are always seen, assessed, and imitated by their children who then will consciously or unconsciously be impregnated then become a habit for their children.Parents or mothers and fathers play an important role and greatly influence the education of their children. since a child was born, it was his mother who was always beside him. Therefore he imitates his mother's temperament and usually, a child is more in love with his mother, if the mother does her job well. This study aims to determine the relationship of parenting students with leadership in MTsN Depok, knowing the relationship of religious guidance of students with leadership in MTsN Depok, and to find out how much the relationship between parenting and religious guidance with the child's leadership in MTsN Depok. The type of research used in this study is quantitative research. The researcher used triangulation or combined data collection techniques, namely different data collection techniques to obtain data from the same source. Analysis of the data used is validity and product moment test. After calculating with Pearson correlation obtained rxy gain of 0.47. At the index 0.40 - 0.70, which means there is a moderate or sufficient correlation between variables X and Y. It turns out the results of